Réponses

2013-12-17T22:30:47+01:00
Bonsoir,

4 ÷ 5 × 15 ÷8 - 7÷8 × 16 ÷21 =

\dfrac{4}{5}\times\dfrac{15}{8}-\dfrac{7}{8}\times\dfrac{16}{21}\\\\=\dfrac{1}{5}\times\dfrac{15}{2}-\dfrac{1}{8}\times\dfrac{16}{3}\\\\=\dfrac{1}{1}\times\dfrac{3}{2}-\dfrac{1}{1}\times\dfrac{2}{3}\\\\=\dfrac{3}{2}-\dfrac{2}{3}\\\\=\dfrac{9}{6}-\dfrac{4}{6}\\\\=\dfrac{5}{6}

2 ÷ 3 - 1 ÷ 6 sur 5 ÷ 4 =

\dfrac{\dfrac{2}{3}-\dfrac{1}{6}}{\dfrac{5}{4}}=\dfrac{\dfrac{4}{6}-\dfrac{1}{6}}{\dfrac{5}{4}}\\\\\\=\dfrac{\dfrac{3}{6}}{\dfrac{5}{4}}\ \ \ =\ \ \ \dfrac{\dfrac{1}{2}}{\dfrac{5}{4}}\ \ \ =\ \ \ \dfrac{1}{2}\times\dfrac{4}{5}\ \ \ =\ \ \ \dfrac{1}{1}\times\dfrac{2}{5}\ \ \ =\ \ \ \dfrac{2}{5}